ANALISIS PENGEMBANGAN KARIER DAN PRESTASI KERJA TERHADAP KUALITAS KINERJA PEGAWAI NEGERI SIPIL DI SEKRETARIAT DPRD KABUPATEN NABIRE - Markus Randan; Baharuddin; Sita Yubelina Sabandar (Paulus Journal of Accounting (PJA), 2024)
This study aims to analyze the influence of career development and work performance on the quality of Civil Servant (PNS) performance at the Nabire Regency DPRD Secretariat. The research method used is quantitative with multiple linear regression analysis, and data processing using SPSS 22. The population of this study consisted of 40 employees, with a sample of 25 people selected using saturated sampling techniques. The results of the study indicate that career development has a positive and significant influence on the quality of PNS performance, emphasizing the importance of investment in human resource development to improve employee performance. However, work performance does not have a significant influence on performance quality, which is likely caused by work environment factors, assessment systems, and employee motivation. Simultaneously, career development and work performance have a significant influence on employee performance quality, indicating that both contribute to increasing the effectiveness of public services in the government environment. The implications of this study point to the need for management to improve the work performance assessment system and improve career development programs in order to achieve more optimal employee performance quality.